A light-up imaging protocol for neutral pH-enhanced fluorescence detection of lysosomal neuraminidase activity in living cells. Issue 87 (14th October 2016) - Bao, Lei; Ding, Lin; Hui, Jingjing; Ju, Huangxian
Abstract : A lysosome-accessing nanoprobe was designed to deliver a Lyso-Neu-specific substrate into lysosomes for neutral pH-enhanced fluorescence detection of Lyso-Neu activity. Abstract : A lysosome-accessing nanoprobe is designed for recognition of lysosomal neuraminidases (Lyso-Neus), which can cleave the 4-methylumbelliferone moieties of the substrate from the nanoprobe, and lead to the escape of the moieties from acidic lysosomes into the neutral cytosol assisted by cationic poly(ethyleneimine) to light up the pH-responsive fluorescence for visual detection and dynamic tracking of Lyso-Neu activity in living cells.